Price change and households’ welfare in Ghana (1991-2013) - Wassiuw, Abdul Rahaman (2017)
Given the growing world population and income in emerging economies, increased demand for food and feed crops for the production of bio-fuels, and greater frequency and intensity of weather-related disasters in different parts of the world due to climate change, global food prices are expected to increase. Food importing developing countries are vulnerable to these price increases and associated price volatility as poor households would be the most severely affected. While there are extensive empirical studies on the effect of food price increases and volatility on household welfare in developed and developing countries, little is known about African countries. This thesis contributes to the literature on Africa, specifically Ghana using three waves of the Ghana Living Standard Survey (GLSS) to measure the effect of food price increases on household welfare between 1991 and 2013 and addressing the effect of price volatility with a measure of households’ willingness to pay for price stability.